Thyroid Hormone Changes in Euthyroid Patients with Diabetes - Qin, Ken (Diabetes Metab Syndr Obes, 2020)
BACKGROUND: Thyroid dysfunction is associated with diabetes, but it is unclear if the thyroid hormone levels change in euthyroid adults with diabetes. OBJECTIVE: To investigate the association between thyroid hormone levels and diabetes in euthyroid adults. METHODS: Among the euthyroid adults who underwent health examination in West China Hospital of Sichuan University in 2016, patients with diabetes were identified according to the medical history, fasting blood glucose and HbA1c. Age and sex matched controls were identified from the population. The patients with diabetes group was further divided into two subgroups: patients with newly diagnosed diabetes (NDD) and with previously diagnosed diabetes (PDD). Independent t-test and multivariate logistic regression models were used to investigate the difference in the levels of thyroid stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3) and the ratio of FT4/FT3 between groups. RESULTS: We included 32,557 participants, 2,271 with diabetes. Compared to the adults without diabetes, the odds ratios (ORs) per one unit elevation of TSH, FT4, FT4/FT3 ratio and FT3 in patients with diabetes were 0.88 [95% confidence interval (CI): 0.82–0.95], 1.11 (95% CI: 1.08–1.14), 2.05 (95% CI: 1.81–2.32) and 0.85 (95% CI: 0.78–0.93), respectively. Compared to the NDD group, the ORs per one unit elevation of TSH, FT4, FT4/FT3 ratio and FT3 of the PDD group were 0.81 (95% CI: 0.71–0.92), 1.08 (95% CI: 1.04–1.12), 1.76 (95% CI: 1.49–2.08) and 1.01 (95% CI: 0.92–1.12), respectively. CONCLUSION: In euthyroid adults, diabetes was associated with increased FT4/FT3 ratio, which is linked to the peripheral turnover of the thyroid hormones.